2017
DOI: 10.1016/bs.acr.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Conceptual Framework to Maximize the Participation of Diverse Populations in Cancer Clinical Trials

Abstract: The underrepresentation of ethnically diverse populations in cancer clinical trials results in the inequitable distribution of the risks and benefits of this research. Using a case study approach, we apply a conceptual framework of factors associated with the participation of diverse population groups in cancer clinical trials developed by Dr. Jean Ford and colleagues to increase understanding of the specific strategies, and barriers and promoters addressed by these strategies, that resulted in marked success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…We found that the representation of blacks among RCT participants has decreased since 2006-2011 in the USA, which is consistent with reviews of race/ethnic representation in other disease states [16]. Reasons for minority under-representation in RCTs are multifactorial and often involve system-level actors-e.g, clinicians, hospitals, and the community [21][22][23][24]. Historical acts of discrimination and marginalization in healthcare settings (e.g., the Tuskegee Syphilis Study) have been hypothesized as reasons why racial minorities are more distrustful of health systems and may also contribute to the under-representation of these groups in RCTs.…”
Section: Discussionsupporting
confidence: 81%
“…We found that the representation of blacks among RCT participants has decreased since 2006-2011 in the USA, which is consistent with reviews of race/ethnic representation in other disease states [16]. Reasons for minority under-representation in RCTs are multifactorial and often involve system-level actors-e.g, clinicians, hospitals, and the community [21][22][23][24]. Historical acts of discrimination and marginalization in healthcare settings (e.g., the Tuskegee Syphilis Study) have been hypothesized as reasons why racial minorities are more distrustful of health systems and may also contribute to the under-representation of these groups in RCTs.…”
Section: Discussionsupporting
confidence: 81%
“…Factors that affect individuals’ willingness to participate in cancer research include perceived benefits, barriers, and facilitators as well as sociodemographic characteristics such as age, race/ethnicity, education, and income [ 18 , 19 , 20 , 21 , 22 ]. Studies assessing the relationships between CHL and willingness to participate in research and donate bio-specimens are lacking among minority populations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important obstacles to clinical research is the difficulty in recruiting and retaining study participants of all ethnic backgrounds. 5 , 6 Historically, Blacks have been disproportionately underrepresented in clinical trials. 7 9 Although incremental progress has occurred since the establishment of the National Institutes of Health (NIH) Revitalization Act, barriers that influence participation of Blacks in research continue to exist.…”
Section: Introductionmentioning
confidence: 99%